O legado do passado, o colapso do presente e a tarefa do futuro : usos da história em "O mito do século XX", de Alfred Rosenberg - Anna Carolina Alves Viana (2022)
This dissertation intends to analyze the writing of history and the temporal relations established in the work "Der Mythus des 20. Jahrhunderts. Eine Wertung der seelisch-geistigen Gestaltenkämpfe unserer Zeit" [The Myth of the 20th Century. An Evaluation of the Spiritual-Intellectual Symbolic Struggles of Our Time], by Alfred Rosenberg. The Nazi regime went to great lengths to rewrite history to legitimize its ideology and actions. Launched in 1930, Rosenberg's work was, in this sense, a relevant theoretical foundation for the worldview that Nazism sought to promote. Its main objective was to base a historical narrative that took the existence of different races and the superiority of the Germanic as palpable realities. This narrative would respond to contemporary yearnings for a new perspective on the past and indicate future directions that would reserve Germany a better situation than the crisis facing the present. Therefore, we seek to analyze the proposal of writing history in "Mythus", having both its historiographical dialogues and its intrinsically mythological nature on the horizon. More specifically, we discuss the mobilizations of the past carried out by the author to shape his argument, the concept of history used in the narrative, and the temporal relations that Rosenberg builds within his work. In addition, we analyze the intellectual trajectory of the author, who is commonly identified as an “ideologist” of National Socialism. Rosenberg occupied this position, but, as we have tried to demonstrate, his trajectory was more complex and broader than the name implies. It can thus reveal new perspectives on the context of the creation of "Der Mythus des 20. Jahrhunderts".